Forensic Linguistic Analysis of Netizens' Hate Speech Acts in Tik-Tok Comment Section - Riska Novita Ria; Teguh Setiawan (Britain International for Academic Research (BIAR) Publisher, 2023)
Hate speech on social media is not new, but existed in traditional media before the rapid development of technology as it is now. Tiktok is a short video social platform powered by music for dance, freestyle or performance. On Tiktok comments there are more comments with hate speech that are insulting, slanderous, and harsh words. The research method in this study uses a qualitative descriptive method. The type of research used is qualitative with a descriptive method that aims to describe acts of hate speech in the comments column on the Tiktok social network. The data in this study are in the form of words and sentences of Indonesian netizens which are hate speech and are uttered in the Tiktok comments column.